The Chemical Abstracts Centennial: Whither CAS? - David Flaxbart (Issues in Science and Technology Librarianship, 2007)
The article reflects on the 100th anniversary of the founding of the Chemical Abstracts Service (CAS) operating at the chemistry department of Ohio State University in Columbus in 2007. A system of chemical nomenclature was established by CAS to aid in indexing and retrieval of chemical substance information. It cites the features of the SciFinder, a client software interface developed by CAS. It states the advantages of using CAS products to libraries.